Bringing the party back in: mobilization and persuasion in constituency election campaigns - Foos, F (2015)
In this thesis, I report the results from the first randomized field experiments conducted in collaboration with party-affiliated candidates and campaigns in the United Kingdom. The papers presented as part of this thesis test both the limits and possibilities of campaign influence, in a partisan political environment. During election campaigns parties provide signals to voters, voluntarily or involuntarily imposing a structure, and thereby constraints, on individuals’ electoral decisions. By integrating insights about heuristic and social decision-making into the experimental campaign literature, I formulate testable hypotheses about the direct and indirect effects of party cues on campaign mobilization and persuasion. The first paper, The Heuristic Function of Party Affiliation in Voter Mobilization Campaigns, addresses how the provision of party cues, used during campaign phone calls, affects turnout among party supporters, opponents and unattached voters. The second paper on Household Partisan Composition and Voter Mobilization, explores the spillover effects from the previous experiment, testing whether campaign-induced mobilization between household members is conditioned by the partisan composition of a household, and the partisan intensity of a campaign message. Paper three investigates if candidates who are Reaching Across The Partisan Divide can win over supporters of rival parties. In the fourth paper, I test if Impersonal, But Noticeable methods of voter contact, such as door hangers and text messages, affect the turnout decisions of partisans and unattached voters. The final paper, The National Effects of Subnational Representation, highlights the importance of local party organization for the outcomes of national elections. The results of this thesis show the electoral consequences of direct and indirect interactions between campaigns and voters of different partisanship, and point to strategies that allow constituency campaigns to successfully navigate challenging partisan environments.